MOTIVATION AND COMPENSATION IN HEALTH SYSTEM - K. N. Borisov; A. O. Subocheva; O. Z. Zasiyeva (Модернизация, инновация, развитие, 2015)
By the defi nition accepted by WHO, «health» it is not simple absence of an illness, but a condition of full physical, moral, mental and social wellbeing. By this defi nition forms of behavior and a way of life of the people, allowing prolonging the period of active, creative and happy life are meant. Health of each person – the main value for modern society. A crisis state of population as open social system, it is shown by its indignation in reply to stressful infl uences of negative socio-economic factors. It is accompanied by change of a condition of the public health which level refl ects depth of occurring changes. In the conditions of market managing also, the policy in the fi eld of compensation, material encouragement and social support of medical workers essentially changes. A certain level of compensation regardless of should be guaranteed to the medical worker, whether mechanisms of economic incentives of its work are used or not. At the same time, the desire of the worker to hold a position with higher salary and desire to work on it is productive and is qualitative – far not same. Increase of material compensation not always leads to increase of labor motivation and aspiration it is better to work. Socially psychological bases of labor motivation of medical workers are those new approaches that will allow solving problems of increase of labor motivation more eff ectively. In article the assessment of labor motivation is analyzed by medical workers, measures for increase of labor motivation and according to improvement of quality of medical care are off ered. The majority of the western experts ineffi ciency of management recognize as the main problem of health care ofRussia. The conclusion that medical institutes, academies and institutes of a post degree obrazoyovaniye, professional development faculties, and, probably, and institutes an upravleyoniya, should adapt foreign experience (motivational, conceptual, technological and organizational and methodical) for retraining old and preparations of new its generation of managers of health care is drawn.